Uropathogenic Escherichia coli Infection Compromises the Blood-Testis Barrier by Disturbing mTORC1-mTORC2 Balance - Lu, Yongning; Liu, Miao; Tursi, Nicholas J.; Yan, Bin; Cao, Xiang; Che, Qi; Yang, Nianqin; Dong, Xi (Frontiers in Immunology, 2021)
The structural and functional destruction of the blood-testis barrier (BTB) following uropathogenic E. coli (UPEC) infection may be a critical component of the pathologic progress of orchitis. Recent findings indicate that the mammalian target of rapamycin (mTOR)-signaling pathway is implicated in the regulation of BTB assembly and restructuring. To explore the mechanisms underlying BTB damage induced by UPEC infection, we analyzed BTB integrity and the involvement of the mTOR-signaling pathway using in vivo and in vitro UPEC-infection models. We initially confirmed that soluble virulent factors secreted from UPEC trigger a stress response in Sertoli cells and disturb adjacent cell junctions via down-regulation of junctional proteins, including occludin, zonula occludens-1 (ZO-1), F-actin, connexin-43 (CX-43)—as well as β-catenin and N-cadherin. The BTB was ultimately disrupted in UPEC-infected rat testes, and blood samples from UPEC-induced orchitis in these animals were positive for anti-sperm antibodies. Furthermore, we herein also demonstrated that mTOR complex 1 (mTORC1) over-activation and mTORC2 suppression contributed to the disturbance in the balance between BTB “opening” and “closing.” More importantly, rapamycin (a specific mTORC1 inhibitor) significantly restored the expression of cell-junction proteins and exerted a protective effect on the BTB during UPEC infection. We further confirmed that short-term treatment with rapamycin did not aggravate spermatogenic degeneration in infected rats. Collectively, this study showed an association between abnormal activation of the mTOR-signaling pathway and BTB impairment during UPEC-induced orchitis, which may provide new insights into a potential treatment strategy for testicular infection.